THU0005 Erap polymorphisms and its association with HLA-B15 and HLA-B27 positive spondylarthritis patients. (15th June 2017) - Londono, J; Santos, AM; Rueda, JC; Peña, P; Briceño, I; Saldarriaga, E-L; Angarita, J-I; Calvo, E; Avila, M; Martinez-Rodriguez, N; Cubides, H; Parra, V; et al.
Abstract : Background: Since 1973, the association of HLA-B27 and spondyloarthritis (SpA) is well known, however in Colombian population it is present in only 40% of patients and HLA-B15 is present almost in 25%. A mechanism of polygenic mechanism has been proposed as an explanation for the development of SpA. Endoplasmic reticulum aminopeptidase (ERAP) genes 1 and 2 have been implicated. ERAP1 is strongly associated with HLA-B27 positive patients and ankylosing spondylitis, but not with ERAP2 Objectives: To determine the association between ERAP polymorphisms and HLA-B27 or HLA-B15 positive SpA patients Methods: 178 patients with SpA according to ASAS criteria were included in the study. HLA typing was performed by the PCR technique using the Biorad® HLA-SSP plates. The polymorphisms were determined by the RT-PCR technique using Roche® probes for ERAP1 rs27044, rs17482078, rs10050860, and rs30187. For ERAP2 the probes used were rs2910686, rs2248374 and rs2549782. The allele and genotype frequencies polymorphisms were obtained by direct counting. In each group the Hardy-Weinberg equilibrium was evaluated using the 2 test. Associations were assessed using odds ratio (OR). Stata v.12.0 program was used to analyse data. The construction and analysis of haplotypes was performed using Haploview v.4.2 Results: In total 70 patients were HLA-B27 positive and 34 were HLA-B15 positive. 78 were women and 100 were men. Linkage disequilibrium map of the ERAP gene is depicted in figure 1 . When analysed by ERAP2 haplotype it is observed that there is a statistically significant association with the combinations described in table 1 . No associations were observed between ERAP1 haplotypes and HLA-B15 or B27 Conclusions: In the group of patients analysed, a statistically significant association was found between patients with SpA HLA-B15 positive and the haplotype TGT of ERAP2. Also HLA-B27 positive SpA patients were associated with haplotype TGC and CAT of ERAP2 with statistical significance Disclosure of Interest: None declared